Standarisasi Perjanjian Baku Pada Perbankan Syariah - Latif, Moh Abdul (Sharia Faculty Islamic Economic Law Study Department, 2019)
The legal relationship applies general terms and conditions set forth in the standard agreement. In connection with the legal relationship between Islamic banks and their customers, they will be questioned, especially those who do not understand the law, what law will be applied in the event of a dispute between Islamic banks and customers regarding the use of an Islamic banking service? Will the existing Islamic law apply to the disputes that arise? Or what will be applied are the terms and conditions set forth in the agreement? This question needs to be raised and the answer is needed to avoid misunderstandings for those who are lawless who intend to connect with Islamic banks, because at this time Indonesia does not yet have Standardization in the form of a Law on standard agreements. therefore it is very necessary to standardize the agreements that apply to the relationship between Islamic banks and their customers by Indonesian banks.